Genetic diversity and transmission pattern of multidrug-resistant tuberculosis based on whole-genome sequencing in Wuhan, China - Liqing Wei; Jun Chen; Zhen Deng; Zefang Zhang; Zhengbin Zhang; Qionghong Duan (Frontiers in Public Health)
BackgroundInvestigating the molecular epidemiological characteristics of multidrug-resistant tuberculosis (MDR-TB) in China’s moderate-burden regions, such as Wuhan, is crucial for understanding and controlling disease transmission.Materials and methodsThis study analyzed MDR-TB isolates from pulmonary tuberculosis cases registered at Wuhan Pulmonary Hospital in 2017. Whole genome sequencing (WGS) was used to identify resistance-conferring mutations, examine their associations with specific Mycobacterium tuberculosis lineages or sublineages, and assess clustering profiles.ResultsAmong the 149 analyzed strains, the most prevalent mutations associated with resistance to 11 anti-tuberculosis drugs were identified as follows: rpoB Ser450Leu (59.73%, rifampicin), katG Ser315Thr (62.42%, isoniazid), embB Met306Val (42.86%, ethambutol), rpsL Lys43Arg (68.13%, streptomycin), pncA Trp68Arg (10.53%, pyrazinamide), gyrA Asp94Gly (22.50%, fluoroquinolones), and rrs 1401A > G (50.00–100.00%, second-line injectable aminoglycosides). Additional mutations were detected in fabG1 c-15C > T (42.86%, ethionamide) and thyX c-16C > T (21.43%, p-aminosalicylic acid). Notably, rare mutations absent from the WHO mutation catalog, such as ahpC c-52C > T and rpsL Lys43Thr, were also observed. The mutation frequency of embB Met306Ile was significantly higher in Lineage 4 (L4) strains than in Lineage 2 (L2) strains (p = 0.0150), while the rpsL Lys43Arg mutation frequency was lower in L4 compared to L2 (p = 0.0333). A total of 31 MDR MTB Mycobacterium tuberculosis isolates formed clusters, resulting in a clustering rate of 20.81% and a recent transmission rate of 11.41%. The clustering rates between L4 and L2 strains were not significantly different (χ2 = 0.0017, p > 0.05).ConclusionThe genetic diversity of MDR-TB in Wuhan demonstrates unique characteristics, with evidence of localized transmission. These findings highlight the urgent need to strengthen measures to detect early cases of MDR-TB and control transmission of MDR-TB in the region.